Pictorial Essay on Ultrasound and Magnetic Resonance Imaging of Paraspinal Muscles for Myofascial Pain Syndrome - Chen‐Yu Hung; Bow Wang; Hsiang‐Chi Chang; Wei‐Ting Wu; Ping‐Tang Liu; Ke‐Vin Chang; Daniel Su; Kamál Mezian; Vincenzo Ricci; Levent Özçakar (2024)
The paraspinal muscles of the cervical, thoracic, and lumbar spine are important pain generators because muscle strains or myofascial pain syndrome caused by trigger points are common during clinical practice. Ultrasonography is the most convenient imaging tool for evaluating these muscles due to its advantages, such as providing good delineation of soft tissues, easy accessibility, and zero radiation. Additionally, ultrasound can serve as a useful guiding tool for paraspinal muscle intervention to prevent inadvertent injuries to vital axial neurovascular structures. This pictorial essay presents ultrasound scanning protocols for the paraspinal and other associated muscles as well as a discussion of their clinical relevance. Axial magnetic resonance imaging has also been used to elucidate reciprocal anatomy. In conclusion, ultrasound imaging proves to be a valuable tool that facilitates the differentiation of individual paraspinal muscles. This capability significantly enhances the precision of interventions designed to address myofascial pain syndrome.